Answer:
Step-by-step explanation:
The point of intersection of
![x+2y=9...eqn1](https://tex.z-dn.net/?f=x%2B2y%3D9...eqn1)
and
is the solution of the two equations.
We add equation (1) and equation(2) to get,
![x+4x+2y-2y=9+-4](https://tex.z-dn.net/?f=x%2B4x%2B2y-2y%3D9%2B-4)
![\Rightarrow 5x=5](https://tex.z-dn.net/?f=%5CRightarrow%205x%3D5)
![\Rightarrow x=1](https://tex.z-dn.net/?f=%5CRightarrow%20x%3D1)
We put
into equation (1) to get,
![1+2y=9](https://tex.z-dn.net/?f=1%2B2y%3D9)
![\Rightarrow 2y=9-1](https://tex.z-dn.net/?f=%5CRightarrow%202y%3D9-1)
![\Rightarrow 2y=8](https://tex.z-dn.net/?f=%5CRightarrow%202y%3D8)
![\Rightarrow y=4](https://tex.z-dn.net/?f=%5CRightarrow%20y%3D4)
Therefore the line passes through the point,
.
The line also passes through the point of intersection of
![3x-4y=14...eqn(3)](https://tex.z-dn.net/?f=3x-4y%3D14...eqn%283%29)
and
![3x+7y=-8...eqn(4)](https://tex.z-dn.net/?f=3x%2B7y%3D-8...eqn%284%29)
We subtract equation (3) from equation (4) to obtain,
![3x-3x+7y--4y=-8-14](https://tex.z-dn.net/?f=3x-3x%2B7y--4y%3D-8-14)
![\Rightarrow 11y=-22](https://tex.z-dn.net/?f=%5CRightarrow%2011y%3D-22)
![\Rightarrow y=-2](https://tex.z-dn.net/?f=%5CRightarrow%20y%3D-2)
We substitute this value into equation (4) to get,
![3x+7(-2)=-8](https://tex.z-dn.net/?f=3x%2B7%28-2%29%3D-8)
![3x-14=-8](https://tex.z-dn.net/?f=3x-14%3D-8)
![3x=-8+14](https://tex.z-dn.net/?f=3x%3D-8%2B14)
![3x=6](https://tex.z-dn.net/?f=3x%3D6)
![x=2](https://tex.z-dn.net/?f=x%3D2)
The line also passes through
![(2,-2)](https://tex.z-dn.net/?f=%282%2C-2%29)
The slope of the line is
![slope=\frac{4--2}{1-2} =\frac{6}{-1}=-6](https://tex.z-dn.net/?f=slope%3D%5Cfrac%7B4--2%7D%7B1-2%7D%20%3D%5Cfrac%7B6%7D%7B-1%7D%3D-6)
The equation of the line is
![y+2=-6(x-2)](https://tex.z-dn.net/?f=y%2B2%3D-6%28x-2%29)
![y+2=-6x+12](https://tex.z-dn.net/?f=y%2B2%3D-6x%2B12)
is the required equation